Acromioclavicular joint instability on cross-body adduction view: the biomechanical effect of acromioclavicular and coracoclavicular ligaments sectioning - Shimpei Kurata; Kazuya Inoue; Takamasa Shimizu; Mitsuyuki Nagashima; Hirakazu Murayama; Kenji Kawamura; Shohei Omokawa; Pasuk Mahakkanukrauh; Yasuhito Tanaka (BMC Musculoskeletal Disorders, 2022)
Abstract Background The acromioclavicular (AC) and coracoclavicular (CC) ligaments are important stabilizers of the AC joint. We hypothesized that AC and trapezoid ligament injuries induce AC joint instability and that the clavicle can override the acromion on cross-body adduction view even in the absence of conoid ligament injury. Accordingly, we investigated how sectioning the AC and CC ligaments contribute to AC joint instability in the cross-body adduction position. Methods Six fresh-frozen cadaveric shoulders were used in this study, comprising five male and one female specimen, with a mean age of 68.7 (range, 51–87) years. The left side of the trunk and upper limb, and the cervical and thoracic vertebrae and sternum were firmly fixed with an external fixator. The displacement of the distal end of the clavicle relative to the acromion was measured using an electromagnetic tracking device. We simulated AC joint dislocation by the sequential resection of the AC ligament, AC joint capsule, and CC ligaments in the following order of stages. Stage 0: Intact AC and CC ligaments and acromioclavicular joint capsule; stage 1: Completely sectioned AC ligament, capsule and joint disc; stage 2: Sectioned trapezoid ligament; and stage 3: Sectioned conoid ligament. The superior clavicle displacement related to the acromion was measured in the horizontal adduction position, and clavicle overriding on the acromion was assessed radiologically at each stage. Data were analyzed using a one-way analysis of variance and post-hoc tests. Results Superior displacement was 0.3 mm at stage 1, 6.5 mm at stage 2, and 10.7 mm at stage 3. On the cross-body adduction view, there was no distal clavicle overriding at stages 0 and 1, and distal clavicle overriding was observed in five cases (5/6: 83%) at stage 2 and in six cases (6/6: 100%) at stage 3. Conclusion We found that AC and trapezoid ligament sectioning induced AC joint instability and that the clavicle could override the acromion on cross-body adduction view regardless of conoid ligament sectioning. The traumatic sections of the AC and trapezoid ligament may lead to high grade AC joint instability, and the distal clavicle may subsequently override the acromion.